Działalność spedycyjna międzynarodowych operatorów logistycznych na przykładzie C. Hartwig Gdynia S.A. i Grupy Raben- analiza porównawcza - Knapik, Natalia (My University, 2015)
Celem pracy jest ukazanie roli operatora logistycznego, oraz porównanie ofert i warunków świadczonych usług dwóch międzynarodowych operatorów logistycznych C. Hartwig Gdynia S.A. oraz Grupy Raben. Działalność obydwóch firm charakteryzuje kompleksowość usług oraz indywidualne podejście do klienta jednak to C. Hartwig Gdynia S.A posiada większe doświadczenie i bogatszą ofertę usługową.

This thesis presents the role of the logistics operator and comparison of services of two international logistics operators C. Hartwig Gdynia S.A and Raben Group. The activities of both companies is characterized by comprehensive services and individual approach to clients but C. Hartwig Gdynia S.A. has more experience and better offer service.
Freight forwarding activity of the international logitics operators on the example of C. Hartwig Gdynia S.A. and Raben Group- comparative analysis
Keywords: spedycja międzynarodowa; operator logistyczny; usługi logistyczne; outsourcing; Grupa Raben; C. Hartwig Gdynia S.A.; international freight forwarding; logistic operator; logistics services; outsourcing; Raben Group; C. Hartwig Gdynia S.A.